Brexit and the battle for financial services. Issue 8 (3rd August 2018) - Howarth, David; Quaglia, Lucia
ABSTRACT: This paper analyses the policy developments concerning the Single Market in finance in the context of Brexit. Theoretically, we engage with two bodies of work that make contrasting predictions on European financial market integration and the development of European Union (EU) policies on financial regulation: one focused upon a neo-mercantilist 'battle' amongst member states and the other stressing the importance of transnational financial networks (or coalitions). Empirically, we find limited evidence of the formation of cross-national alliances in favour of the United Kingdom (UK) retaining broad access to the EU Single Market in financial services, the presence of which would have aligned with the expectations of analyses focused upon transnational networks. By contrast, the main financial centres in the EU27 and their national authorities competed to lure financial business away from the UK – what we explain in terms of a 'battle' amongst member states and their national financial centres.